Consultation Liaison Psychiatry in a Tertiary Care Hospital - Quratulain; Khan , Hazrat Ali; Sherzad , Silsila; Hameed , Abdul; Jaffar, Noorjhan; Muhammad Naseem; Asif , Fiza; kakar , Sana Ullah (Indus Journal of Bioscience Research, 2024)
Background: Consultation-liaison psychiatry (CLP) is a subspecialty that bridges the gap between psychiatry and general medicine, managing the psychiatric needs of patients with physical illnesses in hospital settings. It plays a crucial role in addressing the mental health comorbidities that accompany medical conditions, improving patient care and interdisciplinary collaboration. Objective: This study aims to explore the role of CLP services in a tertiary care hospital, examining the profile of referred patients, their reasons for referral, and the psychiatric diagnoses. It seeks to assess the effectiveness of CLP in addressing psychosocial care needs and enhancing the integration of psychiatric support in medical settings. Methodology: A qualitative approach was adopted, utilizing semi-structured interviews with 220 participants, including patients, healthcare staff, and psychiatric consultants. Data was analyzed to assess patient satisfaction, efficacy of interventions, and the challenges faced by medical professionals in managing psychiatric comorbidities. Results: Among the 220 referred patients, 60% were male. Most referrals came from the general medicine department (52%), followed by pulmonary medicine (12%) and nephrology (9%). The primary reasons for referral included psychiatric evaluation of medically ill patients (38.6%), substance use assessment (18.2%), and evaluation of self-harm/suicidal ideation (13.6%). Mood disorders were the most common psychiatric diagnosis (40.9%). Conclusion: CLP services in the tertiary care hospital provided significant benefits in managing patients with complex medical and psychiatric conditions, highlighting the need for integrated care to improve overall patient outcomes.